Counting and miscounting sheep: genetic evidence for pervasive misclassification of wild fauna as domestic stock - Horsburgh, K. A.; Moreno-Mayar, J. V.; Klein, R. G. (Southern African Humanities, 2017)
The original analyses of faunal assemblages excavated from Blydefontein Rock Shelter, Karoo in 1967 (Sampson) and 1985 (Bousman) were undertaken by Klein and Cruz-Uribe and did not identify remains of domestic stock. Reanalysis of the 1985 faunal assemblage by Scott and Plug found the remains of domestic stock. Ten specimens were morphologically identified as sheep or sheep/goat. One of those specimens identified as a domestic caprine yielded a direct radiocarbon determination of 2860–2765 cal. BP, some 800 years older than any other evidence of domestic stock in the region. Eight of the specimens identified as domestic stock were provided for ancient DNA analysis, and we were able to recover DNA from five of them. Mitochondrial genome sequencing allowed us to identify one of the specimens morphologically identified as sheep/goat to sheep, and identify four other such specimens as originating in indigenous southern African bovid species. Crucially, the specimen purported to provide evidence of surprisingly early domestic stock in southern Africa came instead from an eland. Two recently published papers have challenged the authenticity of the genetic results. The challenges, however, are rooted in significant misunderstandings of molecular genetics.